2022
DOI: 10.21009/jdmb.05.2.3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of E-Service Quality and Brand Trust on Repurchase Intention with Customer Satisfaction as Intervening for Telemedicine Application Users

Abstract: As an intervention for Halodoc application users, this study aims to determine the impact of telemedicine application product e-service quality and brand trust  on  customer satisfaction repurchase intent. We surveyed 245 users of  Halodoc applications who performed transactions using Halodoc applications at least once in the past year. The data analysis method used SPSS version 23 and the SEM analysis used LISREL 8.8 to process and analyze the survey data. Hypothesis test results  show that quality of e-servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 5 publications
3
8
0
Order By: Relevance
“…Research conducted by Elim and Santoso (2022) shows that customer satisfaction has a significant effect on repurchase intentions, indicated by a p-value of 0.000 and a T-statistic value of 6.982, which means a pvalue <0.05 and a t-statistic > 1.96. Meanwhile, research conducted by Udayana et al (2022) shows that customer satisfaction does not affect repurchase intentions, indicated by a t-count of -1.148 and a significant level of 0.254 > 0.005 in a negative direction. Therefore the researcher takes the following hypothesis: H4.…”
Section: The Effect Of Customer Satisfaction On Repurchase Intentionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Research conducted by Elim and Santoso (2022) shows that customer satisfaction has a significant effect on repurchase intentions, indicated by a p-value of 0.000 and a T-statistic value of 6.982, which means a pvalue <0.05 and a t-statistic > 1.96. Meanwhile, research conducted by Udayana et al (2022) shows that customer satisfaction does not affect repurchase intentions, indicated by a t-count of -1.148 and a significant level of 0.254 > 0.005 in a negative direction. Therefore the researcher takes the following hypothesis: H4.…”
Section: The Effect Of Customer Satisfaction On Repurchase Intentionsmentioning
confidence: 95%
“…Research conducted by Hutapea et al (2022) shows that website quality has a positive and significant effect on repurchase intentions, indicated by the positive value of the website quality regression coefficient of 0.220, meaning that every increase of one unit of website quality will increase repurchase intentions by 0.220 with a probability value of 0.007 or significantly at the level (α =<5%) 0.05. Research conducted by Udayana et al (2022) shows that website quality has a positive and significant effect on repurchase intentions, indicated by website quality having a t-count of 3.269 and a significant level of 0.002 <0.05 in a positive direction. Meanwhile, research conducted by Mavilinda and Nazaruddin (2022) shows that website quality cannot affect repurchase intentions, as indicated by the results of the hypothesis test obtained a negative value of -0.090 and a p-value > 0.05, which is 0.089.…”
Section: Effect Of Website Quality On Repurchase Intentionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This data implies that the level of ease of use is still relatively low, which is less than 50%. Melinda et al (2023) also in their research resulted in the effect of usability variables on satisfaction only being 43.7%. When connected, the effect on loyalty and word of mouth decreases.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, when seen in this light, the banking system is an essential component of the contemporary economy (Baum et al, 2023). This is the era of electronic banking, where customers can easily transfer funds through the exchange of electronic singles rather than exchanges of cash (Melinda et al, 2023). To gain market advantages, the banks invest a large amount of money in the use of modern technology to retain their customers.…”
Section: Introductionmentioning
confidence: 99%